Salivary Chromium and Cobalt Concentrations in Patients with Dental Metallic Restorations-A Pilot Study - Zlatina Tomova; Desislav Tomov; Delyana Davcheva; Yordanka Uzunova (MDPI AG, 2024)
Introduction: Metal ions, released from dental alloys due to corrosion, come in contact with the cells of the surrounding tissues and may spread throughout the body via the gastrointestinal system, thus inducing dose-dependent cytopathological effects. This study aimed to assess and compare the salivary cobalt and chromium concentrations in individuals aged 18-65 years with and without dental restorations containing metal alloys. Methods: Participants were divided into two main groups according to the existence of metal alloys in the oral cavity-18 patients had fixed prosthetic restorations made of metal alloys, and 17 patients had no metal objects in their oral cavity. Each main group was subdivided into two subgroups according to the type of saliva sample-with or without additional stimulation. Salivary cobalt and chromium concentrations were measured by inductively coupled plasma mass spectrometry. A non-parametric Mann-Whitney test and Spearman's rank correlation coefficient were applied, and the level of significance was set to p < 0.05. Results: The results showed that the chromium level in non-stimulated saliva was higher in the group of patients with metal dental restorations. No statistical difference was found in cobalt levels. There was no statistical difference in Co or Cr concentrations in stimulated saliva between the studied groups. A positive correlation was found between Cr and Co concentrations in non-stimulated saliva and between cobalt concentrations in stimulated and non-stimulated saliva. Conclusions: Metal alloys in the oral cavity induced elevated chromium levels in non-stimulated saliva, and a correlation between chromium and cobalt ion concentration was found. A detailed examination of patients and their medical history prior to prosthetic treatment is advisable in order to avoid any undesired health effects.